Non-ideal theory in the philosophy of religion: Exploring implications of non-ideal theorising for the problem of evil - Echazú, Gabriel (Religious studies, 2026)
This article explores the implications of non-ideal theorising for the problem of evil. The critique of ideal theory - which has gained increased attention in several philosophical sub-disciplines during recent years - states that analytic philosophers tend to rely on overly idealised conditions, to the point of being completely unrealistic, in their theorising. To investigate if this charge holds merit in the philosophy of religion, I apply a non-ideal methodology to one traditional area of philosophy of religion - the problem of evil. Here, Richard Swinburne’s theodicy constitutes a sample of how the problem of evil is typically approached in mainstream philosophy of religion. Additionally, Swinburne’s Principle of Credulity will, in relation to his theodicy, be interrogated as well. Applying non-ideal theorising, I find that Swinburne’s theorisation relies on idealised cases and presupposes ideal conditions, while overlooking non-ideal realities. Turning to epistemic injustice and epistemology of ignorance, I find that Swinburne assumes ideal epistemological conditions in both inter-agent communication (testimony), and in collective cognition. After examining the implications of such idealisations, I find that Swinburne’s idealisations abstract away non-ideal factors which are relevant for his theories, concluding that Swinburne displays tendencies typical of ideal theorising.